STUDIES ON GENETICS FOR YIELD AND STORABILITY OF POTATO - Pradhan, A M; Sarkar, K K; Konar, A (Potato Journal, 2015)
Globally potato (Solanum tuberosum L.) is an important food crop which saves millions of hungry people in developing countries. Sometimes over production forces Indian farmers for distress sale due to lack of storage facilities or expensive cold storage. The problem may be solved by developing potato genotypes which can be stored in country storage with minimum loss. Twelve potato genotypes were evaluated for yield and its attributing characters along with storage factors by harvesting potatoes at two different growth phases (75 and 90 days after planting (DAP). Analysis of variance following split plot design revealed presence of significant differences on yield and storage characters. Higher production of marketable tubers was found in K-22 and in Kufri Khyati and MS-1/4353. From total storage study minimum storage loss for different factors was noticed in MS-1/4353 and Kufri Pushkar. These genotypes can be considered in breeding for extended shelf-life under country storage with high yield. Marketable tubers showed maximum direct effect on yield and similarly sprouting loss and desiccation loss revealed maximum direct influence on total tuber loss accompanied by additive gene effect.